CMS Full Simulation for Run-2. Issue 7 (December 2015) - Hildreth, M; Ivanchenko, V N; Lange, D J; Kortelainen, M J
Abstract: During LHC shutdown between run-1 and run-2 intensive developments were carried out to improve performance of CMS simulation. For physics improvements migration from Geant4 9.4p03 to Geant4 10.0p02 has been performed. CPU performance has been improved by introduction of the Russian roulette method inside CMS calorimeters, optimization of CMS simulation sub-libraries, and usage of statics build of the simulation executable. As a result of these efforts, CMS simulation has been speeded up by about factor two. In this work we provide description of updates for different software components of CMS simulation. Development of a multi-threaded (MT) simulation approach for CMS will be also discuss.